Sport and society a student introduction - Houlihan, Barrie (London : SAGE, 2008)
Organized around themes of exclusion and opportunity, commercialism and the global arena of sport, this edition provides much-needed coverage of the relations between sport practice, social policy and the social contexts in which both occur.
Previous ed.: 2003.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Sports -- Social aspects